Psychiatrization of Resistance: The Co-option of Consumer, Survivor, and Ex-patient Movements in the Global South - Logan, Jenny; Karter, Justin M. (Frontiers in Sociology, 2022)
This article examines contemporary examples of psychiatrization as a tool of disciplinary control and repression, focusing on new research on the co-option of consumer/survivor/ex-patient movements within the Global South. Here, we understand psychiatrization as (1) the process of imposing certain interpretive limits on states of difference and distress and (2) the conceptualization of treatment and recovery through the teleological notion of normalcy. By interpreting difference solely in psychiatric terms, psychiatrization functions as a tool of disciplinary control in both domestic and international contexts by reterritorializing efforts to resist hegemonic norms and political institutions of gendered and racialized oppression, colonialism, and imperialism. After setting out our understanding of psychiatrization as a political process in the sense that it enacts a particular “ontological politics” (Mol, 1999), one that foregrounds psychiatric interpretations of difference and dissent to the exclusion of other possible meanings, we examine the reach and complexity of psychiatrization in the suppression of political and social movements that attempt to resist oppressive norms and institutions. We then present new research within the consumer/survivor/ex-patient and psychosocial disability movements in the Global South to show how psychiatrization can thwart activist’s aims of transforming how we view both the end goals of mental health treatment and the political valence of mental distress.